In Situ Monitoring of Rolling Circle Amplification on a Solid Support by Surface Plasmon Resonance and Optical Waveguide Spectroscopy - Lechner, Bernadette; Hageneder, Simone; Schmidt, Katharina; Kreuzer, Mark P; Conzemius, Rick; Reimhult, Erik; Barišić, Ivan; Dostalek, Jakub (ACS applied materials & interfaces, 2021)
The growth of surface-attached single-stranded deoxyribonucleic acid (ssDNA) chains is monitored in situ using an evanescent wave optical biosensor that combines surface plasmon resonance (SPR) and optical waveguide spectroscopy (OWS). The "grafting-from" growth of ssDNA chains is facilitated by rolling circle amplification (RCA), and the gradual prolongation of ssDNA chains anchored to a gold sensor surface is optically tracked in time. At a sufficient density of the polymer chains, the ssDNA takes on a brush architecture with a thickness exceeding 10 μm, supporting a spectrum of guided optical waves traveling along the metallic sensor surface. The simultaneous probing of this interface with the confined optical field of surface plasmons and additional more delocalized dielectric optical waveguide modes enables accurate in situ measurement of the ssDNA brush thickness, polymer volume content, and density gradients. We report for the first time on the utilization of the SPR/OWS technique for the measurement of the RCA speed on a solid surface that can be compared to that in bulk solutions. In addition, the control of ssDNA brush properties by changing the grafting density and ionic strength and post-modification via affinity reaction with complementary short ssDNA staples is discussed. These observations may provide important leads for tailoring RCA toward sensitive and rapid assays in affinity-based biosensors.
Keywords: biosenzitivní techniky; DNA, Single-Stranded; polyelectrolyte brushes; optické jevy; DNA; Time Factors; Biosensing Techniques; Optical Phenomena; Surface Plasmon Resonance; spektrální analýza; biointerfaces; surface plasmon-enhanced fluorescence; rolling circle amplification; optical waveguide spectroscopy; časové faktory; jednovláknová DNA; Spectrum Analysis; povrchová plasmonová rezonance; Nucleic Acid Amplification Techniques; techniky amplifikace nukleových kyselin; surface plasmon resonance